The relationship between internet addiction and schema mechanisms among adolescents - Aksoy, Feyza; Ünübol, Hüseyin (Journal of Dependence, 2021)
Objective: The aim of this study was to investigate the relationship between internet addiction and schema mechanisms of adolescents in a private high school sample. Method: The study sample was based on a relational screening model with the participation of 148 volunteer students in a private Anatolian High School located in Üsküdar district of Istanbul province in the 2015-2016 Academic year. Data was collected using the Internet dependency scale, Young schema scale, and sociodemographic data form. Results: The sample consists of 148 students, 75 of whom are girls, 72 of whom are boys, and 1 person who has not stated their gender, representing 14-18 age group who continue their education in their classes. There was no difference between internet addiction and gender, while there are significant differences between age groups. According to the purpose of using the Internet, addiction is highest in recreational use. In addition, a positive directional relationship was found between internet dependence and schema mechanisms. Conclusion: Among 18 maladjusted schemas found in adolescents in the study group, a positive moderate strong relationship was found between imperfection, inadequate self-control and submissiveness schemas and internet addiction.